Resistance Reactions to Meloidogyne trifoliophila in Trifolium repens and T. semipilosum - Mercer, Chris F. (Society of Nematologists, 2004)
The predominant root-knot nematode in New Zealand pastures is Meloidogyne trifoliophila, and a recurrent selection program in Trifolium repens has developed resistance to this species. No data are available, however, on the mechanisms of resistance in T. repens or resistant genotypes of T. semipilosum. The development of M. trifoliophila in roots of T. repens and T. semipilosum was examined weekly after a 2-day inoculation with eggs. More second-stage juveniles (J2) were found in two resistant genotypes of T. repens than in two susceptible ones 1 week after inoculation. J2 did not develop further in resistant genotypes, but in susceptible plants development proceeded to the adult stage, visible at 4 weeks after inoculation. The mode of action of resistance to M. trifoliophila in T. repens and in T. semipilosum was compared after a 24-hour inoculation with J2. Numbers of J2 per root tip ranged from 0 to 12 with a median of one for each species. At 24 hours after inoculation (HAI), similar numbers of J2 were seen in the cortex oriented toward the root tip in both resistant and susceptible genotypes of both plant species. At 48 HAI, accumulations of J2 were seen in the meristem in both resistant and susceptible genotypes of both plant species. At 72 HAI, differences in nematode responses were evident between resistant and susceptible genotypes of both plant species; in susceptible roots, J2 heads were embedded in the developing stele. At this time, a browning reaction in resistant genotypes of both plant species indicated a hypersensitive response, and differences in the reaction were recorded between T. repens and T. semipilosum. More study is needed to determine whether the resistance reaction in T. semipilosum is suitable for introgression or insertion into T. repens.